Sector specific sources of competitiveness in the Western Balkans : recommendation for a regional investment strategy - Organisation for Economic Co-operation and Development; SourceOECD (Online service) ([Paris] : OECD, 2008)
The Western Balkan region benefits from a cost-competitive labor force and geographic and cultural proximity to EU markets. However, cost competitiveness as a source of differentiation is not sustainable. Cost levels are increasing gradually in some sectors, reducing firms' profitability. In order to sustain competitiveness, the Western Balkans needs to move up the value chain, from investing in automated technology to producing higher-quality goods and enhancing its human capital. This report examines the apparel manufacturing, automotive components and business process and technology outsourcing sectors, focusing on market competitiveness factors, industry key success factors and policy recommendations.--Publisher's description.
pt. 1. Approach and methodology -- pt. 2. Sector analysis and policy recommendations. Apparel manufacturing -- Automotive components -- Business process and information technology outsourcing -- pt. 3. Recommendation for a regional competitiveness initiative. Regional competitiveness initiative.
Includes bibliographical references.
Also available online.
Keywords: Competition -- Balkan Peninsula -- Statistics; Investments -- Balkan Peninsula -- Statistics; Industrial policy -- Balkan Peninsula -- Case studies; Technological innovations -- Balkan Peninsula; Quality of products -- Balkan Peninsula; Labor supply -- Balkan Peninsula; Regional economics; Balkan Peninsula -- Economic conditions; Balkan Peninsula -- Economic policy